Outreach Activities by Universities as a Channel for Science Communication - Davis, Lloyd Spencer (Communicating Science to the Public, 2014)
Universities engage in outreach activities about science for a variety of reasons, including enhancing their reputation, recruitment and the personal satisfaction of those involved. Be that as it may, such activities are typically portrayed as a form of science communication whereby the public is informed about science. Outreach activities may be classified according to their costs, their reach (i.e. the audience size) and their persistence (i.e. the duration of the activity and how long it is available to the public). When costs of many activities traditionally favoured by universities as outreach for science are weighed against their reach and persistence, they prove not to be the most effective forms of outreach in terms of the value they provide. Encouraging and facilitating staff (and, where appropriate, students) to engage in interviews about science with the media as well as to popularise science – through writing books and articles for the popular press and, where possible, being involved in documentaries about science – are amongst the most effective means by which universities can communicate science to the public. Enhancing such practices will require universities to recognise and reward staff for popularising science, rather than rewarding only publications and citations in scientific journals. Online outreach activities are also an area of great potential when it comes to persistence and the size of the audience: promoting science on the university’s website, encouraging staff to write blogs or contribute to group blogs or forums about science and posting material about science to iTunes U are some of the most cost-effective ways to communicate science to the public. When using more traditional forms of outreach – such as public talks, café scientifiques and U3A – their effectiveness may be enhanced if they occur regularly or are packaged as a group of activities in a way that the public can subscribe to them. Talks in schools, often treated as a source of potential recruitment by universities, can also be viewed as critical for helping to reverse a developing trend in recent times of disinterest in science amongst secondary school pupils. Finally, there may be social reasons favouring outreach activities by universities that go beyond a simple cost-benefit analysis, such as engaging indigenous peoples in science.